Penyuluhan Literasi Digital bagi Ibu-Ibu PKK Kelurahan Kedaung Kecamatan Pamulang Tangerang Selatan - Sari, Ratna; Putri, Shafira Nursyah; Choirunnisa, Choirunnisa (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
This article aims to narrate the community service process carried out by a team of lecturers from the Communication Studies Program at Pamulang University in Kedaung Village, Pamulang District, South Tangerang City, Banten. The community service in this article raises the theme of digital literacy counseling, especially for women's groups. The unstoppable development of information and communication technology has brought complex changes to every sector of life. Without gender dichotomy, men and women have equal opportunities to participate and even become the main actors in the use of information technology. They easily access and obtain information from anywhere without exception. However, unfortunately, the flood of information they receive is not accompanied by digital ethics. As a result, some of them, especially women, become serious targets for the spread of news or consumption of misleading information. To address this, digital literacy counseling for them is essential. This community service method uses a counseling model or lectures for local PKK mothers. The results of the community service show that they realize that the culture of origin for the information they receive has become the root of the rampant female victims of false news. They also realized the importance of ensuring the accuracy of the information they received so that in the future, women's groups would become a safe group in digital media.